2012
DOI: 10.1590/s1806-37132012000300014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da infecção pelo HIV em pacientes com tuberculose na atenção básica em Fortaleza, Ceará

Abstract: O objetivo deste trabalho foi determinar a prevalência da infecção pelo HIV em indivíduos com > 15 anos de idade e diagnóstico confirmado de tuberculose, acompanhados em Centros de Saúde da Família de Fortaleza (CE). Uma amostra aleatória de 110 pacientes com diagnóstico de tuberculose de 26 Centros de Saúde da Família foi incluída no estudo, realizado entre os meses de janeiro e maio de 2009. Todos os participantes responderam a um questionário com dados sociodemográficos e clínicos e realizaram so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The predominant occupation was janitorial services, 49.3% (310), with health professionals present portion of the cases 2.4% (15). In the sample of this study, it was observed that HIV (14.6%), and diabetes mellitus (10.4%) are among the main pathologies, although the greater number of patients did not register comorbidities (62%).…”
Section: Methodsmentioning
confidence: 62%
“…The predominant occupation was janitorial services, 49.3% (310), with health professionals present portion of the cases 2.4% (15). In the sample of this study, it was observed that HIV (14.6%), and diabetes mellitus (10.4%) are among the main pathologies, although the greater number of patients did not register comorbidities (62%).…”
Section: Methodsmentioning
confidence: 62%